Factors associated with Burnout Syndrome in medical students - Hana Fernandes Tavares, Helen; Rodrigues Soares da Silva, Heloísa; Maria Melo Miranda, Isabela; Santana Braga, Monise; de Oliveira Santos, Raquel; Silva Guerra, Heloísa (O Mundo da Saúde, 2020)
Burnout syndrome can be defined as a syndrome of emotional exhaustion, depersonalization and reduced personal fulfillment, related to high emotional demands at work. Burnout syndrome has also been observed in medical students, as they are exposed to several stressors. The number of studies involving aspects of the university public is still low which are crucial for development of research to elucidate the knowledge of this profile. The aim of this study was to identify the prevalence of Burnout syndrome among medical students and the factors associated with this condition. This was a cross-sectional study with 419 students enrolled from the second to the eighth semester of the medical course at a public university in the State of Goiás. The instruments used were the Maslach Burnout Inventory - Student Survey (MBI-SS) and a sociodemographic and lifestyle questionnaire. As a result, this study found that 9.5% of medical students had changes in the three dimensions of the instrument, suggesting the presence of Burnout syndrome, with scores for the dimensions of exhaustion, disbelief and professional effectiveness being 3.6; 1.7 and 4.3, respectively. Of the factors associated with this condition, the most prominent were the frequent use of stimulating substances, the use of tobacco and alcohol. Therefore, interventions are necessary with pedagogical and psychological support as well as encouraging family life, in order to minimize the possible negative impacts of this condition on students' lives.